Circadian Control of Sodium and Blood Pressure Regulation. (24th June 2021) - Soliman, Reham H; Pollock, David M
Abstract: The attention for the control of dietary risk factors involved in the development of hypertension, includes a large effort on dietary salt restrictions. Ample studies show the beneficial role of limiting dietary sodium as a lifestyle modification in the prevention and management of essential hypertension. Not until the past decade or so have studies more specifically investigated diurnal variations in renal electrolyte excretion, which led us to the hypothesis that timing of salt intake may impact cardiovascular health and blood pressure regulation. Cell autonomous molecular clocks as the name implies, function independently to maintain optimum functional rhythmicity in the face of environmental stressors such that cellular homeostasis is maintained at all times. Our understanding of mechanisms influencing diurnal patterns of sodium excretion and blood pressure has expanded with the discovery of the circadian clock genes. In this review, we discuss what is known about circadian regulation of renal sodium handling machinery and its influence on blood pressure regulation, with timing of sodium intake as a potential modulator of the kidney clock.